Effect of Copper Electrode Geometry on the Electrical Characteristics of Electrolytic Analysis Cell Used for Pure Metal Production - Naji, Noor Izzuddin (Al-Nahrain Journal of Science, 2018)
In this work, the effect of geometry of copper electrode employed in electrolytic analysis cell used for metal purification was studied. These effects are apparent when studying the electrical characteristics of such cell as the geometry of the electrode determines the most important parameters of an electrolytic analysis cell; electric field and current density. Three different geometries of the electrodes were considered in this work. To produce mass amount of pure metal, large surface electrodes have to be used at reasonably higher concentrations of hydrochloric acid, while the variation of acetic acid concentration causes little variation in current density and hence produced amount of pure metal. Highly increasing rate of current densities would be achieved but the electrolyte would be changed to undesired or inapplicable form since the conductivity of the electrolyte is very sensitive to the changes in concentration. The electrolytic analysis cells are efficiently used to prepare highly pure metals in electrolyte solutions.